Age at onset of caloric restriction and its effects on the redox profile of the rat hippocampus. Issue 1 (December 2016) - Pereira, Cristiane; Nardin, Patricia; de Souza, Daniela; Grings, Mateus; Leipnitz, Guilhian; Gonçalves, Carlos; Schneider, Augusto; Abib, Renata; Valle, Sandra; Helbig, Elizabete
Abstract Background The benefits of caloric restriction (CR) on the protection against age-related neurodegenerative diseases have been the subject of several studies. However, the effects of CR on the central nervous system are still poorly understood since most studies were carried out in mature animals. The present study aimed to investigate whether the age at onset of CR could differently affect the redox status of the rat hippocampus. Methods Thirty-two male Wistar rats at 35 days old (35d;n  = 16) and 65 days old (65d;n  = 16) were fed ad libitum or subjected to 30 % CR (n  = 8 group/age) for 12 weeks. At the end of the experiment, the rats were euthanized, blood was collected, and the hippocampus was dissected for measuring the redox status. Results CR in 35d and 65d rats induced a 16 and 21 % reduction in body weight gain, respectively, compared to controls (p  < 0.05). Urea, total cholesterol, triacylglycerol, HDL cholesterol, and LDL cholesterol concentrations were lower in CR 35d rats than in 35d controls (p  < 0.05). No differences were detected between the CR groups and controls in the object recognition test (p  > 0.05) and in superoxide dismutase activity, nitric oxide content, and lipid peroxidation levels (p  > 0.05). However, glutathione peroxidase activity was higher (p  < 0.0001) in 65d rats compared to that in 35d rats, and GSH content was higher (p  < 0.05) in CR-fed rats compared to that in controls at both ages. Conclusions In conclusion, CR increased GSH content when started at both ages but did not affect the activity of antioxidant enzymes and the level of ROS in the hippocampus. In addition, CR did not induce any detrimental effects on memory and nutritional status when started in both 35d and 65d rats.